Wisdom Passed Down Through the Ages - Tripses, Jenny Susan; Lazaridou, Angeliki (Frontiers in Education, 2020)
Women have always played influential leadership roles in education but cultural notions have frequently limited their roles to behind-the-scenes contributions. The result is that their voices and wisdom have not been fully appreciated by subsequent generations. We propose to tell the stories of two women ˗ one Greek, the other American ˗ who lived in the 19th century as a way to more fully understand who women educators are, where we have come from, and where we are going. We selected these two women ˗ Aikaterini Laskaridou and Lydia Moss Bradley ˗ because their legacies continue to have a powerful influence on education even today, over a century after their deaths. The authors seek in the paper (1) to provide deeper understandings of their lives and accomplishments, and (2) to relate the understandings gained from their stories to current understandings of how women educators have influenced contemporary societies. The relevance of our endeavor is summed up by Elias Xirotiris (1961) who recently wrote about one of our subjects “since Laskaridou’s death, there [has been] no one to take the baton and to continue her work with the same enthusiasm and dedication.” We hope that our paper will contribute to a better appreciation of the considerable legacies left by the subjects of our investigation.